2022
DOI: 10.1186/s12877-022-03187-0
|View full text |Cite
|
Sign up to set email alerts
|

Medicines use before and after comprehensive medicines review among residents of long-term care facilities: a retrospective cohort study

Abstract: Background Residential Medication Management Review (RMMR) is a subsidized comprehensive medicines review program for individuals in Australian residential aged care facilities (RACFs). This study examined weekly trends in medicines use in the four months before and after an RMMR and among a comparison group of residents who did not receive an RMMR. Methods This retrospective cohort study included individuals aged 65 to 105 years who first entered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…A significant number of studies supporting a decrease in the rates of DRPs and PIMs were of particular interest, thus prompting this study to examine the characteristics of the included articles. There was no substantial variation in sample sizes across the selected articles, except for the study by Sluggett et al 8) which was conducted with a large sample size of 11,309 participants. This variation is attributed to the cohort study design employed in the study.…”
Section: Rate Of Incidence Of Drug-related Problems and Potentially I...mentioning
confidence: 99%
See 1 more Smart Citation
“…A significant number of studies supporting a decrease in the rates of DRPs and PIMs were of particular interest, thus prompting this study to examine the characteristics of the included articles. There was no substantial variation in sample sizes across the selected articles, except for the study by Sluggett et al 8) which was conducted with a large sample size of 11,309 participants. This variation is attributed to the cohort study design employed in the study.…”
Section: Rate Of Incidence Of Drug-related Problems and Potentially I...mentioning
confidence: 99%
“…Most articles included in this review indicated that pharmacists' medication reviews did not significantly affect the rate of hospitalization (Table 3). 8,11,12,17,18,21, Most articles discussing hospitalization focused on medication re-views without any additional interventions. However, three studies by Kua et al 29) in 2020, Santolaya-Perrín et al, 30) and Zwietering et al 31) included other healthcare professionals such as geriatricians and nurses as part of the medication review process.…”
Section: Hospitalizationmentioning
confidence: 99%
“…Comprehensive medicines reviews are one potential strategy to limit antipsychotic initiation and trigger deprescribing. However, few individuals accessing HCP or PRAC receive comprehensive medicines reviews, 57 and the modest impact this stand‐alone intervention has on overall antipsychotic use suggests additional supportive interventions may be required 58 . There is some evidence that multifaceted interventions informed by behavior change theories can support successful withdrawal of antipsychotics in PRAC settings 46,59 and resources to guide review, tapering and withdrawal are available 60,61 .…”
Section: Discussionmentioning
confidence: 99%
“…Additional limitations included the inability to ascertain appropriateness of antipsychotic use, use for managing symptoms at end‐of‐life, or reasons for cessation. Consistent with other analyses of prescription claims data that do not capture dosing instructions, 35,58 prescription durations were derived from claims data (based on the number of days in which three‐quarters of individuals receive a prescription refill) to estimate antipsychotic duration of use; hence overestimation or underestimation is possible. Our analysis presumes that all medicines dispensed were consumed which means exposure misclassification is also possible for (i) individuals who ceased treatment and did not consume the full quantity dispensed or (ii) those who restarted therapy soon after treatment cessation.…”
Section: Discussionmentioning
confidence: 99%